2021
DOI: 10.48550/arxiv.2101.09608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The design of the Ali CMB Polarization Telescope receiver

Maria Salatino,
Jason E. Austermann,
Keith L. Thompson
et al.

Abstract: Ali CMB Polarization Telescope (AliCPT-1) is the first CMB degree-scale polarimeter to be deployed on the Tibetan plateau at 5,250 m above sea level. AliCPT-1 is a 90/150 GHz 72 cm aperture, two-lens refracting telescope cooled down to 4 K. Alumina lenses, 800 mm in diameter, image the CMB in a 33.4 • field of view on a 636 mm wide focal plane. The modularized focal plane consists of dichroic polarization-sensitive Transition-Edge Sensors (TESes). Each module includes 1,704 optically active TESes fabricated on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…So we obtain a ∼ 78% sky coverage patch for the space-based CMB experiment showed in the upper panel of figure 1. Second, we consider the AliCPT-1 experiment (Li et al 2017;Salatino et al 2021), a CMB experiment in the northern hemisphere, to represent of…”
Section: Simulation Setupmentioning
confidence: 99%
“…So we obtain a ∼ 78% sky coverage patch for the space-based CMB experiment showed in the upper panel of figure 1. Second, we consider the AliCPT-1 experiment (Li et al 2017;Salatino et al 2021), a CMB experiment in the northern hemisphere, to represent of…”
Section: Simulation Setupmentioning
confidence: 99%
“…We assume this is the observed sky patch with f sky ∼ 78.8%, which is representative of a 2 https://github.com/LSSTDESC/NaMaster space-based polarization experiment. In addition, we consider a f sky ∼ 15.1% sky patch in the northern hemisphere, based on the AliCPT-1 experiment (Li et al 2017;Salatino et al 2021), for the observed sky of the ground-based experiment simulations. We show the binary mask for these two sky patches in figure 1.…”
Section: Simulation Setup and Idealized Testsmentioning
confidence: 99%
“…Great effort has been made to observe the CMB B-modes with ongoing ground-based experiments, such as BICEP-3 (Ahmed et al 2014), AdvACTPol (Henderson et al 2016) and SPT-3G (Benson et al 2014). Other upcoming experiments, like AliCPT-1 (Li et al 2017;Salatino et al 2021), Simons Observatory (Ade et al 2019), LSPE (The LSPE collaboration et al 2012), QUIJOTE (Pérez-de-Taoro et al 2014) and CMB-S4 (The CMB-S4 Collaboration et al 2020), will join the efforts to look for the primordial CMB B-mode from the ground, while the future LiteBIRD (Hazumi et al 2019) satellite aims to observe the CMB polarized signal from space.…”
Section: Introductionmentioning
confidence: 99%